Hubungan Aktivitas Luar Ruangan dengan Miopia Mahasiswa Kedokteran Angkatan 2019 Universitas Andalas - Nabila Alifina; Kemala Sayuti; Ulya Uti Fasrini (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background: Myopia or nearsightedness is a condition in which light entering the eye is focused in front of the retina, resulting in the blurry appearance of distant objects. This can be caused by disturbances in the regulation of eye growth that can be hereditary or coming from the environment, for example from outdoor activities. Based on research in 2017 in Beijing stated that more frequent outdoor activities can reduce the risk of myopia.Objective: The purpose of this study was to analyze the relationship between outdoor activity and myopia in medical students of Andalas University batch 2019.Methods: This is an analytic study with a case-control design through consecutive sampling techniques. The sample consisted of 60 respondents, 30 of them which suffered myopia and another 30 with ametropia. Data was collected using a questionnaire that has been tested for validity. Outdoor activities, namely all activities carried out in the wild or outdoors and exposed to sunlight for approximately three hours per day. The processing of the data was done with a statistical chi-square test.Results: 45% of the respondents with outdoor activity less than three hours have myopia and 5% of respondents with outdoor activity more than three hours have myopia. Statistical chi-square test was performed to see the relationship between outdoor activity and myopia with p-value = 0.001 (p <0.05).Conclusion: It was concluded that there was a significant relationship between outdoor activity and myopia in medical students of Andalas University batch 2019.